Mechanisms and inhibitors of ferroptosis in psoriasis - Zhou, Qiao; Yang, Lijing; Li, Ting; Wang, Kaiwen; Huang, Xiaobo; Shi, Jingfen; Wang, Yi (Frontiers in Molecular Biosciences, 2022)
Psoriasis is a chronic inflammatory skin disease that features localized or widespread erythema, papules, and scaling. It is common worldwide and may be distributed throughout the whole body. The pathogenesis of psoriasis is quite complex and the result of the interplay of genetic, environmental and immune factors. Ferroptosis is an iron-dependent programmed death that is different from cell senescence, apoptosis, pyroptosis and other forms of cell death. Ferroptosis involves three core metabolites, iron, lipids, and reactive oxygen species (ROS), and it is primarily driven by lipid peroxidation. Ferrostatin-1 (Fer-1) is an effective inhibitor of lipid peroxidation that inhibited the changes related to ferroptosis in erastin-treated keratinocytes and blocked inflammatory responses. Therefore, it has a certain effect on the treatment of psoriatic lesions. Although ferroptosis is closely associated with a variety of human diseases, such as inflammatory diseases, no review has focused on ferroptosis in psoriasis. This mini review primarily focused on the pathogenesis of psoriasis, the mechanisms of ferroptosis, the connection between ferroptosis and psoriasis and ferroptosis inhibitors in psoriasis treatment. We discussed recent research advances and perspectives on the relationship between ferroptosis and psoriasis.